Changes in the choroidal thickness in reproductive-aged women with iron-deficiency anemia - Yumusak, Erhan (BMC Ophthalmol, 2015)
BACKGROUND: The aim of this study was to investigate the potential significance of the central macular thickness (foveal thickness-FT) and choroidal thickness (CT) in the eyes of patients with iron-deficiency anemia, the most common form of the anemia, via enhanced-depth imaging optical coherence tomography (EDI-OCT). We also investigated whether such changes might serve as an early indicator of underlying hematological disease. METHODS: This prospective clinical study compared 96 female patients with iron-deficiency anemia and 60 healthy female control subjects. The macular and choroidal thicknesses in the temporal and nasal subfoveal areas were measured using enhanced-depth imaging optical coherence tomography (EDI-OCT) at 500 and 1500 microns and in five different regions (FCT, T(1500), T(500), N(500), and N(1500)). RESULTS: The mean ages of the patients and healthy controls were 34.08 ± 10.39 years and 32.29 ± 8.28 years, respectively (P =0.232). There were no significant changes in macular thickness between the groups (225.58 ± 19.76 vs. 222.45 ± 13.51, P =0.2). The choroidal thickness was significantly reduced in the patient group relative to the controls at all measured points (foveal choroidal thickness, P = 0.042; nasal–500 microns, P = 0.033; temporal–500 microns, P = 0.033; and temporal–1500 microns, P = 0.019). At some points, the choroidal thickness findings correlated with the hemoglobin values (temporal–500 microns, r = −0.287, P = 0.001; nasal–500 microns, r = −0.287, P = 0.005; nasal–1500 microns, r = −0.245, P = 0.016; and temporal–1500 microns, r = −0.280, P = 0.06). CONCLUSIONS: Patients with iron-deficiency anemia had a significantly reduced choroidal thickness.